Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte

Nanophase CulnS(2) nanosheets/CuS composite grown by the SILAR method leads to high performance as a counter electrode in dye sensitized solar cells - Bhosale, Reshma K.; Agarkar, Shruti A.; Agrawal, Ishita; Naphade, Rounak A.; Ogale, Satishchandra (RSC Advances, 2014)
Single phase CulnS(2) (CIS) nanosheets are synthesized on TiO2 coated FTO by the simple technique of Successive Ionic Layer Adsorption Reaction (SILAR) followed by annealing at 500 degrees C. Annealing at a lower temperature of 250 degrees C is found to yield CuS nanoparticles in addition to the CIS phase. Both single phase CIS and the CuS/CIS nanocomposite were examined as counter electrodes for a dye-sensitized solar cell (DSSC). The CIS-CuS composite is found to have a synergistic effect on the catalytic performance toward the reduction of tri-iodide, yielding a power conversion efficiency of 6.3% as compared to pristine CIS (5%) or CuS (3.5%). The possible reasons behind the high performance of the composite are elucidated using cyclic voltammetry (CV) measurements and electrochemical impedance spectroscopy (EIS).

Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.